(untitled) (Global Journal of Human-Social Science, 2023)
During the Corona Virus Disease 2019 Pandemic all the schools in China were suspended under the requirement from the Ministry of Education of China and then the online education were spreading all over China This research is aimed to analyze the utility of online education in China during this time-sensitive situation in light of constructivism learning theory try to find out the pros and cons of online education and then estimate the development of online education in the future